2006
DOI: 10.1002/hrm.20114
|View full text |Cite
|
Sign up to set email alerts
|

The HR competencies‐HR effectiveness link: A study in Taiwanese high‐tech companies

Abstract: This article explores the relationship between HR competencies and HR effectiveness as perceived by line managers and employees within 39 surveyed Taiwanese high‐tech firms. The data were collected from multiple constituencies in the form of four targeted surveys, and the analysis was conducted at the firm level. Respondents included 182 high‐level executives, 152 HR managers, 320 line managers, and 1,262 employees. Results suggest that in the Taiwanese high‐tech context, HR competencies of field expertise and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 20 publications
0
72
0
3
Order By: Relevance
“…Collins & Smith, 2006;Detert, Schroeder, & Cudeck, 2003;Ebesutani, Okamura, Higa-McMillan, & Chorpita, 2011;Garb, Wood, & Fiedler, 2011;Glisson & James, 2002;González-Romá, Peiró, & Tordera, 2002;Han, Chou, Chao, & Wright, 2006;Hatami, Motamed, & Ashrafzadeh, 2010;Keller, 2001;Law, Shek, & Ma, 2011;Merrell, Felver-Gant, & Tom, 2011;Nelson, Canivez, Lindstrom, & Hatt, 2007;Oliver, Jose, & Brough, 2006;Patterson et al, 2005;Philips et al, 2006;Raspa et al, 2010;Riordan, Vandenberg, & Richardson, 2005;Robert & Wasti, 2002;Salanova, Agut, & Peiró, 2005;Schaubroeck, Lam, & Cha, 2007;Takeuchi, Lepak, Wang, & Takeuchi, 2007;C. M. Tucker et al, 2011;van der Vegt & Bunderson, 2005;Zohar & Tenne-Gazit, 2008) and only a few studies that properly account for clustering (Breevaart, Bakker, Demerouti, & Hetland, 2012;Jackson, Levine, & Furnham, 2003;Mathisen, Torsheim, & Einarsen, 2006;Subramony, Krause, Norton, & Burns, 2008;Wang, Willett, & Eccles, 2011).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
See 1 more Smart Citation
“…Collins & Smith, 2006;Detert, Schroeder, & Cudeck, 2003;Ebesutani, Okamura, Higa-McMillan, & Chorpita, 2011;Garb, Wood, & Fiedler, 2011;Glisson & James, 2002;González-Romá, Peiró, & Tordera, 2002;Han, Chou, Chao, & Wright, 2006;Hatami, Motamed, & Ashrafzadeh, 2010;Keller, 2001;Law, Shek, & Ma, 2011;Merrell, Felver-Gant, & Tom, 2011;Nelson, Canivez, Lindstrom, & Hatt, 2007;Oliver, Jose, & Brough, 2006;Patterson et al, 2005;Philips et al, 2006;Raspa et al, 2010;Riordan, Vandenberg, & Richardson, 2005;Robert & Wasti, 2002;Salanova, Agut, & Peiró, 2005;Schaubroeck, Lam, & Cha, 2007;Takeuchi, Lepak, Wang, & Takeuchi, 2007;C. M. Tucker et al, 2011;van der Vegt & Bunderson, 2005;Zohar & Tenne-Gazit, 2008) and only a few studies that properly account for clustering (Breevaart, Bakker, Demerouti, & Hetland, 2012;Jackson, Levine, & Furnham, 2003;Mathisen, Torsheim, & Einarsen, 2006;Subramony, Krause, Norton, & Burns, 2008;Wang, Willett, & Eccles, 2011).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…M. Tucker et al, 2011) and macro-level units (mostly in organizational studies; Babakus et al, 2004;C. J. Collins & Smith, 2006;Glisson & James, 2002;González-Romá et al, 2002;Han et al, 2006;Keller, 2001;Patterson et al, 2005;Riordan et al, 2005;Robert & Wasti, 2002;Salanova et al, 2005;Schaubroeck et al, 2007;Takeuchi et al, 2007;van der Vegt & Bunderson, 2005;Zohar & Tenne-Gazit, 2008). Because micro-level constructs are very unlikely to illuminate macro-level constructs (Klein & Kozlowski, 2000) and disaggregated analysis represents the relations among variables in micro-level units (uncontrolled for macro-level units), we do not focus on comparing the results from disaggregated data with macro-level parameters.…”
Section: Effects Of Ignoring Clusteringmentioning
confidence: 97%
“…Furthermore, it was supported by Guest (2001), employer reports on the HRM effectiveness from their perspective as a manager, not from their experience of the actual practices-they are not the consumers of HRM, the employee are. Unlike many studies of HRM which are based on data supplied solely by HR managers, studies adopting the multiple constituency perspective necessarily include assessments of HRM effectiveness by non-HRM staff (Geare Edgar, & Deng, 2006;Han, Chou, Chao, & Wright, 2006;Kane, Crawford, & Grant, 1999;Mitsuhashi, Park, Wight, & Chua, 2000;Teo & Crawford, 2005;Wright, McMahan, Snell, & Gerhart, 2001). Therefore, collecting data from HR manager as well as line manager is likely to enhance the reliability of findings reported in studies on HRM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The HR contributions component is evaluated on how the HR function was being run and how it was contributing to the firm on different dimensions (e.g., how HR contributed to the firm's competitive position, bottom line, core competence, and human capital). These two aspects of HRM effectiveness has been used and validated in the past studies (Han et al, 2006;Mitsuhashi et al, 2000;Wright et al, 2001). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed a strategic HR role might not be desirable or feasible across all organisations (Caldwell, 2003;Guest & King, 2004). Utilisation varies in the US and UK (Chartered Institute of Personnel and Development [CIPD], 2007;Lawler & Mohrman, 2003) and in non-Western economies such as Taiwan (Han, Chou, Chao, & Wright, 2006) and Oman (Mamman & Al Kulaiby, 2014), while Rasmussen et al (2010) found that only 40-60% of HR departments in Western economies are involved with strategy issues from the outset.…”
Section: The Relationship Between Strategic and Functional Hr Competementioning
confidence: 96%